My one and only cowboy - Pine, A. J.; Brown, Carolyn, 1948- (Forever, 2019)
Delaney Harper thought she'd seen the last of Meadow Valley two years ago after she divorced her lying, cheating, gambler of a husband who left her broken-hearted and, well, just flat broke. But news that her ex sold their property---without legally removing her from the deed---means heading back to claim her share of the land---and possibly her dream. Sam Callahan, co-owner of the Meadow Valley guest ranch, is barely keeping his head above water. He bought the land for a steal, but keeping a new business afloat is another story. When a gorgeous blonde barges onto his property on a quiet Friday afternoon insisting he bought the place in a fraudulent sale---and that she's there to prove she still owns half the land---Sam realizes he's got much more to worry about. He could lose everything---including his heart.